Mandando bocas: Woo and Sex among Sampadjudu Young Men - Miguel, Francisco (Revista de Antropología Social, 2016)
In this paper I deal with a Cape Verdean phenomenon: the mandar bocas (“to send mouths”). Specifically, I analyse the action of “mandar bocas” made by men in the town of Mindelo. At a first glance, this phenomenon could be quickly classified as “homophobic” slurs. I argue, however, that this is not the only possible interpretation of the phenomenon as “mandar bocas” is often a phase of a homoerotic courtship between young men in Cabo Verde, though permeated by masculinist signs.